Outdoor mobility in senior housing residents and community-dwelling older people in different population density areas - Sini Siltanen; Essi-Mari Tuomola; Markku Kauppinen; Kirsi E. Keskinen; Taina Rantanen; Mikaela von Bonsdorff (BMC, 2024)
Abstract Background Outdoor mobility supports functioning and active life in old age. There is scarce knowledge about the outdoor mobility of senior housing residents, and it remains unclear whether outdoor mobility is dependent on one's home location. Aims We investigated outdoor mobility among senior housing residents and community-dwelling older adults in different population-density areas. Methods We pooled data from two Finnish studies: a senior housing survey (N = 322) and a population-based cohort study among community-dwelling older adults (N = 1018). Life-space mobility (higher score indicating greater mobility) and autonomy outdoors (lower score indicating greater autonomy) were used as markers of outdoor mobility. Population density was used as an indicator of service availability and outdoor mobility enabling infrastructure. Data were analyzed with linear regression and moderation analyses. Results The mean life-space mobility scores were 70.5 (standard deviation, SD 20.0) among community-dwelling older adults and 54.8 (SD 27.6) among senior housing residents. For autonomy outdoors, the scores were 5.3 (SD 3.7) and 7.4 (SD 4.9), respectively. Population density moderated the association of housing type with outdoor mobility. In the highest and lowest population-density areas, senior housing residents had lower life-space mobility and poorer autonomy outdoors than community-dwelling older adults, whereas in the intermediate population-density areas, no such differences were found. Conclusions The location of a senior house is meaningful and optimal for outdoor mobility when within easy reach but not too near amenities. Poorer outdoor mobility among senior housing residents may reflect their adjustment to a new home environment and life situation, e.g., becoming a widow.